MAINTAINING NATION SOLIDITIES THROUGH RENEWABLE ENERGY MANAGEMENT BASED ON MUTUAL COOPERATION - Khotimah, Khusnul (Jurnal Pertahanan dan Bela Negara, 2019)
The community is one of the potential sources for building solidity, strength and defense for the Indonesian people. However, building on the condition of the Indonesian nation's solidity in the midst of current globalization has many challenges. One of them is by trying to condition people who are united in maintaining the solidity of the nation. The research method in this study used literature studies and previous research observation of the author. The result is an analysis of the role of community solidity in managing renewable energy towards energy independence supporting national defense forces, through the implementation of basic energy self-management including: (1) awareness of the importance of citizen solidity in managing renewable energy through solid community participation in a community so as not only normative appeals, but there needs to be clear regulations regarding the active involvement of the community in supporting the 23% renewable energy mix program in 2025; (2) the community becomes the driving force of solidarity in energy management that has succeeded in facilitating other communities in providing energy independently and contributing to the growth of people's economy in supporting national defense. Keywords: Community Solidity, Energy, Self-Management